Literatur Review: Analisis Praktik Pembelajaran Fisika untuk Mengembangkan Kemampuan Berpikir Kritis Siswa - Yonatan Vari; Toni Dwi Fauzi (Lembaga Bale Literasi, 2026)
Students' Critical Thinking Skills are one of the skills needed in the development of 21st-century skills, where students are trained to process and evaluate information objectively, and reach appropriate and effective decisions. This skill can be developed through physics learning, among others. This study discusses how physics learning practices in an effort to develop students' critical thinking skills. This study uses a Systematic Literature Review Approach, with the following steps: 1) searching for articles, 2) selecting articles based on year, 3) selecting articles based on keywords, and 4) selecting articles based on practice. From this process, 135 articles were obtained that were relevant to the title in this study, with details of 53 articles related to the use of learning tools and 82 articles related to the use of learning models. Based on the results of the analysis, it was found that the learning tools most frequently used as support were media (24%), LKPD (19%), and virtual laboratories (15%). The most widely used learning models were PBL (32%), Discovery/Inquiry (18%), and PjBL (11%). Conclusion from this research can be used as a reference for researchers and educators to choose models or learning tools that can be used to develop students' critical thinking skills in physics learning.The approach that has a small percentage in the researcher's findings requires further research to find various possibilities for implementing other learning models that can help in developing students' critical thinking skills.